Kuat Tekan Beton Dan Waktu Ikat Semen Portland Komposit (PCC) - Azmi Firnanda; Alex Kurniawandy; Ermiyati Ermiyati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
This research comparison compressive strength and setting time of concrete used Portland Cement Composite (PCC) and Ordinary Portland Cement (OPC). Total of samples are 120 and for each ages are 10. Composition of mixture in this research base on ACI method. The result of the test obtained compressive strength of PCC at the age of 3, 7, 14, 21, 28, and 90 days are 15.65, 21.54,  27.69, 31.37,  31.71 and 37.65 then for OPC are16.99, 22.65, 28.99, 32.27, 32.89, and 38.16. Research showed the age factor of PCC for each ages are 15.65, 21.54, 27.69, 31.37, 31.71, and 37.65 then for OPC are 16.99, 22.65, 28.99, 32.27, 32.89, and 38.16. The value  of age factor OPC and PCC obtained different with the age factor OPC on PB 89 standard. The initial setting time of PCC are 119.17 minute and OPC are 92,99 while the final setting time of PCC are 165 minute and OPC are 150 minute. Keywords: age factor, compressive strength, PCC, OPC, setting time.